Nurse(s) make a Difference on Early Detection of Intimate Partner Violence (IPV) in Pregnancy: A Study Case - Toraman, Aynur; Daghan, Safak (JPAIR Multidisciplinary Research, 2014)
Violence against women in the perinatal period is common and leads to negative health outcomes for women and infants. This case presentation demonstrates the value of home visit interventions and nursing implications for abused pregnant woman. A single case study was utilized in this research. The only participant in this study was Canan K.*, a 20 year-old pregnant living in Izmir, Turkey. Home visiting interventions addressing intimate partner violence in perinatal period have been effective in minimizing intimate partner violence and improving outcomes. In this case, the nursing educators and primary health care nurse served as an advocate for the abused woman, supporting her in her decision-making and providing necessary resources and referrals.